Factors affecting job performance employees: a qualitative study in Johor Area - Lee Zhen, Yan (Universiti Malaysia Sarawak, 2019)
The study aims to investigate the factors affecting job performance employees in Johor. The specific objectives are to identify the supervisor's perceptions towards employee's performance; to identify the factors that affect employees in job performance and to study the challenges faced by the organization to enhance the employee's performance. The case study design is adopted in the study and semi-structured interview has been implemented as an instrument to collect data. Purposive sampling is used to get the most suitable informants for this study. The findings revealed that the supervisor's perceptions towards employee's performance need to be improved. The findings also identify the factors that affect employees in job performance which included compensation, job satisfaction, and human resource management. The challenges faced by the organization to enhance the employee's job performance is lacking training and development, lacking communication and time management. Last but not least, the findings are important for the employees and the HR practitioner to aware of the importance of maintaining and improve job performance. Besides, HR practitioners shall suggest the management of the organization to organize the workshops or events related to the importance of job performance.